Legal Implications of Blank Column for Participation and Pilkada Results in Indonesia - Ahmad Riyadi Akili Adam; Zamroni Abdussamad; Mohamad Rivaldi Moha (Yayasan Cerdas Pedia Indonesia, 2026)
This study examines the legal implications of blank columns (empty boxes) on voter participation and electoral outcomes in Indonesia’s single-candidate regional elections (Pilkada). Utilizing normative legal research with statutory and case approaches, this paper analyzes how the blank column operates within the constitutional framework of local democracy. The findings indicate that while the blank column procedurally protects voting rights by preventing the automatic victory of single candidates, it fundamentally highlights a structural deficit in substantive democracy due to a severe lack of political competition. Furthermore, a blank column victory legally disrupts governance continuity, necessitating the appointment of unelected interim regional heads. Consequently, this study demonstrates that the blank column functions merely as a post-facto corrective mechanism rather than a preventive solution for flawed candidate recruitment. It concludes that Indonesian electoral design requires substantial reform to foster genuine political contestation and safeguard substantive democratic legitimacy.